Carbon dioxide emission reducing cement composition and cementitious hardened body
Patent Information
- Application Number
- JP2022096052
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-06-14
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-06-14
Smart Images

Figure 0007943728000018 
Figure 0007943728000019 
Figure 0007943728000001
Abstract
Description
[Technical Field]
[0001] This invention relates to cement that produces low carbon dioxide emissions during cement production (hereinafter referred to as "carbon dioxide emission-reducing cement"), etc. The term "cementaceous hardened body" includes mortar and concrete. [Background technology]
[0002] To mitigate global warming, various methods have been proposed to reduce carbon dioxide emissions, which are the main cause of global warming. One such method involves using the reaction between cement hydrate, which is produced during the manufacturing process of cementitious hardened materials such as concrete, and carbon dioxide, to allow the mixture or hardened material to absorb carbon dioxide.
[0003] For example, Patent Document 1 proposes a concrete mixture containing one or more powder components, such as γ-C2S (2CaO·SiO2) and steelmaking slag powder, and Portland cement, wherein the total amount of γ-C2S powder and steelmaking slag powder is 25-95% by mass, and the water-cement ratio is 80-250%. Furthermore, Patent Document 2 proposes a cementitious hardened body obtained by carbonating a hardened cement mixture containing (A) a powdered cement composition containing either or both mullite and anorthite, and Portland cement, (B) water, and (C) aggregate. Furthermore, Patent Document 3 proposes a cementitious hardened body obtained by carbonizing a cement mixture containing (A) 100 parts by mass of C2S (2CaO·SiO2), 10 to 200 parts by mass of C2AS (2CaO·Al2O3·SiO2), and 20 parts by mass or less of C3A (3CaO·Al2O3), a powdered cement composition containing Portland cement, (B) water, and (C) aggregate. Furthermore, since all of the aforementioned cementitious hardened bodies absorb a large amount of carbon dioxide during the curing process, the total amount of carbon dioxide emitted can be reduced. Here, the total amount of carbon dioxide emitted refers to the amount of carbon dioxide emitted during the cement manufacturing process minus the amount of carbon dioxide absorbed during the curing process of the cementitious hardened body. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2011-168436 [Patent Document 2] Japanese Patent Publication No. 2016-153357 [Patent Document 3] Japanese Patent Publication No. 2016-47788 [Patent Document 4] Patent application No. 2021-207628 [Overview of the Initiative] [Problems that the invention aims to solve]
[0005] The present inventors have applied for a hydraulic composition, etc., that can reduce total carbon dioxide emissions by accelerating the hydration of cementitious hardened materials in the early stages of age (1 day of age), thereby allowing the generated hydrate to absorb more carbon dioxide (Patent Document 4). However, in order to further curb global warming, the present invention aims to provide carbon dioxide emission-reducing cement, etc., that produces even less carbon dioxide during cement production. [Means for solving the problem]
[0006] This invention, as a result of diligent research to solve the above problems, is 2CaO·Al2O3·SiO 2、A cement containing 4CaO·Al₂O₃·Fe₂O₃, 2CaO·SiO₂ that sustains a hydration reaction over a long period of time, and admixtures such as blast furnace slag was found to be able to solve the aforementioned problems, leading to the completion of the present invention. That is, the present invention relates to a carbon dioxide emission-reducing cement and the like having the following constitution.
[0007] [1] A carbon dioxide emission-reducing cement composition comprising 43 to 82 parts by mass of ordinary Portland cement relative to 100 parts by mass of the following (A) carbon dioxide emission-reducing cement. (A) Carbon dioxide emission-reducing cement: a cement comprising 52 to 174 parts by mass of fine blast furnace slag powder relative to 100 parts by mass of the following (B) C₂AS-containing cement (B) C₂AS-containing cement: a cement comprising a calcined product containing the following (a) to (c) and gypsum (a) Relative to 100 parts by mass of 2CaO·SiO₂, 3CaO·Al₂O₃ is 0 quality parts by mass (b) Relative to 100 parts by mass of 2CaO·SiO₂, the total amount of 2CaO·Al₂O₃·SiO₂ and 4CaO·Al₂O₃·Fe₂O₃ is 30~49.4 parts by mass (c) Relative to 100 parts by mass of 2CaO·Al₂O₃·SiO₂, 4CaO·Al₂O₃·Fe₂O₃ is 0 to 0.61 parts by mass [2] A cementitious hardened body comprising 25 to 70 parts by mass of water and an aggregate relative to 100 parts by mass of the carbon dioxide emission-reducing cement composition described in the above [1]. [3] The cementitious hardened body according to the above [2], wherein the aggregate is an aggregate in which carbon dioxide is fixed to one or more selected from the group consisting of clinker aggregate, recycled aggregate, waste concrete, blast furnace slag, and steelmaking slag. [4] The cementitious hardened body according to the above [2] or [3], wherein the cementitious hardened body is a carbonation-cured cementitious hardened body. [5] The cementitious hardened body according to the above [4], which is a cementitious hardened body that fixes 80 to 200 kg of carbon dioxide per 1 m 3 of the cementitious hardened body. (Effects of the Invention)
[0008] The carbon dioxide emission-reducing cement of the present invention has lower carbon dioxide emissions during cement production, and can reduce the total carbon dioxide emissions. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] [Figure 1] This is a diagram showing the cutting positions of mortar specimens and concrete specimens. [Figure 2] This is a diagram showing the measurement positions for the neutralization depth of mortar specimens and concrete specimens. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0010] As described above, the present invention is a carbon dioxide emission-reducing cement and the like, which comprises a calcined product containing the aforementioned (a) to (c), and one or more admixtures selected from fine blast furnace slag powder, fine limestone powder, fly ash, fresh concrete sludge, and fine waste concrete powder. For the sake of simplicity in the subsequent description, 2CaO·SiO₂ is abbreviated as C₂S, 3CaO·Al₂O₃ as C₃A, 2CaO·Al₂O₃·SiO₂ as C₂AS, and 4CaO·Al₂O₃·Fe₂O₃ as C₄AF hereinafter. Hereinafter, the present invention will be described separately for the carbon dioxide emission-reducing cement, cement composition, cementitious hardened body, and method for producing the calcined product.
[0011] 1. Carbon dioxide emission-reducing cement The carbon dioxide emission-reducing cement of the present invention is a carbon dioxide emission-reducing cement comprising a calcined product containing the following (a) to (c), and one or more admixtures selected from fine blast furnace slag powder, fine limestone powder, fly ash, fresh concrete sludge, and fine waste concrete powder.
[0012] (a) The content of C₃A is 0 to 15 parts by mass relative to 100 parts by mass of C₂S. It is difficult to manufacture fired products with a C3A content exceeding 15 parts by mass, and the fluidity decreases when used in mortar or concrete. The C3A content is preferably 0 to 10 parts by mass, more preferably 0 to 5 parts by mass, per 100 parts by mass of C2S.
[0013] (b) For every 100 parts by mass of C2S, the total amount of C2AS and C4AF is 10 to 100 parts by mass. If the total content of C2AS and C4AF is less than 10 parts by mass per 100 parts by mass of C2S, the amount of C2S, which has a slower hydration reaction, will be high, and carbonation will not progress, resulting in low carbon dioxide absorption in the early stages of the material's lifespan. If it exceeds 100 parts by mass, the proportion of C2S will decrease, resulting in low carbon dioxide absorption over the long term. The total content of C2AS and C4AF is preferably 20 to 90 parts by mass, more preferably 30 to 80 parts by mass, per 100 parts by mass of C2S.
[0014] (c) C4AF is 0 to 210 parts by mass relative to 100 parts by mass of C2AS. When the C4AF content exceeds 210 parts by mass per 100 parts by mass of C2AS, the initial hydration activity decreases. The C4AF content in the calcined product of the present invention is more preferably 0 to 120 parts by mass, and even more preferably 10 to 100 parts by mass, per 100 parts by mass of C2AS. Furthermore, the mineral composition of the calcined product (the proportion of C2S, C3A, C2AS, and C4AF, etc.) can be quantified by Rietveld analysis after fitting the theoretical profile of each mineral to the powder X-ray diffraction chart (measured profile) of the clinker powder of the present invention. Commercially available analysis software can be used for this quantification. In addition, quantification can also be performed by microscopic observation or point counting using electron backscatter diffraction.
[0015] Next, the mixed materials such as blast furnace slag powder used in the present invention will be described below. (i) Blast furnace slag fine powder The blast furnace slag fine powder used in this invention includes pulverized water-granulated slag obtained by rapidly cooling and crushing molten slag, a by-product of pig iron production in a blast furnace, with water. Furthermore, the basicity of the blast furnace slag fine powder is preferably 1.7 or higher, more preferably 1.75 or higher, and even more preferably 1.8 or higher. If the basicity is 1.7 or higher, the strength development is further improved. The basicity is calculated using the following formula (A). Basicity = (CaO + MgO + Al2O3) / SiO2 ... (A) However, the chemical formula in the formula represents the content (mass %) of the compound represented by that chemical formula in the blast furnace slag fine powder.
[0016] The Blaine specific surface area of the blast furnace slag fine powder is preferably 2500 to 7000 cm². 2 / g, more preferably 3500~6000cm 2 / g, more preferably 4000-5000cm 2 The value is / g. The Braine specific surface area is 2500 cm². 2 If the value is above / g, the strength development of mortar and concrete will be further improved, reaching 7000cm². 2 If the value is less than / g, the fluidity and workability of mortar and concrete will be further improved.
[0017] (ii) Fine limestone powder The calcium carbonate content in the limestone fine powder used in this invention is preferably 90% by mass or more, more preferably 95% by mass or more. When the content is 90% by mass or more, the strength development is further improved. In addition, the production method of the fine limestone powder is not particularly limited, and for example, fine powder produced by pulverizing natural limestone, fine powder produced by reacting carbon dioxide in boiler exhaust gas discharged into the atmosphere with highly alkaline wastewater, or fine powder obtained by carbonating fresh concrete sludge or concrete powder can be used. However, from the perspective of reducing carbon dioxide emissions during cement production, fine powder produced by reacting carbon dioxide in boiler exhaust gas with highly alkaline wastewater, or fine powder obtained by carbonating fresh concrete sludge or concrete powder is preferred. These fine powders fix carbon dioxide present in exhaust gas or the atmosphere, and are carbon-negative materials (a state where the amount of absorbed carbon dioxide is greater than the amount of carbon dioxide emitted during production). Therefore, by using them as a blending material, carbon dioxide emissions during cement production can be reduced.
[0018] The Blaine specific surface area of the fine limestone powder is preferably 2500 to 25000 cm 2 / g, more preferably 3000 to 20000 cm 2 / g, still more preferably 4000 to 15000 cm 2 / g, still more preferably 4200 to 10000 cm 2 / g, particularly preferably 4500 to 9500 cm 2 / g. When the Blaine specific surface area is 2500 cm 2 / g or more, the strength development of mortar and concrete is further improved, and when it is 25000 cm 2 / g or less, the fluidity and workability of mortar and concrete are further improved.
[0019] (iii) Fly ash The fly ash used in the present invention includes one or more selected from raw coal ash, Class I, Class II, Class III, and Class IV fly ash specified in JIS A 6201, and pulverized products thereof. The Blaine specific surface area of the fly ash is preferably 2000 to 12000 cm 2 / g, more preferably 2500 to 8000 cm 2 / g, still more preferably 3000 to 6000 cm 2 / g, particularly preferably 3500-5500 cm 2 The value is / g. 2 If the value is less than / g, the strength of mortar and concrete may decrease, and 12,000 cm² 2 If the price exceeds [amount] / g, cement becomes more expensive.
[0020] Furthermore, the vitrification rate of the fly ash is preferably 85% or less, more preferably 80% or less, and even more preferably 75% or less. The vitrification rate of the fly ash and the equivalent amount of minerals in the fly ash (mineral composition) can be determined using methods such as the Rietveld method (XRD), microscopy using a polarizing microscope, and the XRD internal standard method.
[0021] (v) ready-mix concrete sludge The ready-mix concrete sludge used in this invention is obtained by sieving sludge generated during the concrete manufacturing process at ready-mix concrete plants and concrete product plants using a sieve with an appropriate mesh size, thereby collecting it as a fine powder containing cement hydrate and cement unhydrate. The cement hydrate and cement unhydrate contained in ready-mix concrete sludge are easily carbonated in carbon dioxide and in the slurry during the production of calcium carbonate, and since the CaO content is 30% by mass or more, it absorbs a large amount of carbon dioxide.
[0022] (vi) Waste concrete fine powder The waste concrete powder used in this invention is a fine powder containing cement hydrate and unhydrated cement, obtained by crushing concrete waste generated during the demolition of concrete structures and then removing aggregate from the crushed material. Since the other properties of waste concrete powder are the same as those of fresh concrete sludge, waste concrete powder is easily carbonated, and because its CaO content is 15% or more, it absorbs a large amount of carbon dioxide.
[0023] The Brain specific surface area of the entire mixed material is preferably 2000 to 10000 cm². 2 / g, more preferably 2500~8000cm 2 / g, more preferably 3000-6000cm 2 It is / g. If the Blaine specific surface area is within this range, the fluidity and strength development of mortar and concrete will be excellent.
[0024] Furthermore, the carbon dioxide emission-reducing cement of the present invention is preferably a cement containing 10 to 95 parts by mass of blast furnace slag fine powder, 0 to 30 parts by mass of limestone fine powder, and 0 to 25 parts by mass of fly ash per 100 parts by mass of the carbon dioxide emission-reducing cement. When the content of each component is within the above range, the fluidity and strength development of the mortar and concrete are excellent.
[0025] Furthermore, the carbon dioxide emission-reducing cement of the present invention may contain gypsum in an amount of 0 to 6.0% by mass in terms of SO3. If the gypsum content exceeds 6.0% by mass, the strength of the cementitious hardened body using the carbon dioxide emission-reducing cement may decrease. The gypsum content is preferably 1.0 to 3.0% by mass in terms of SO3. Furthermore, the gypsum is not particularly limited and may be one or more selected from dihydrate gypsum, α-type hemihydrate gypsum, β-type hemihydrate gypsum, and anhydrous gypsum, etc. Furthermore, there are no particular limitations on the method of mixing the calcined material and gypsum, and examples include a method of simultaneously crushing the calcined material and gypsum, or a method of crushing the calcined material and then mixing the crushed material with gypsum.
[0026] 2. Cement composition The cement composition of the present invention contains 65 to 300 parts by mass of the carbon dioxide emission-reducing cement per 100 parts by mass of Portland cement or Portland cement clinker. If the content of the carbon dioxide emission-reducing cement is less than 65 parts by mass, the amount of carbon dioxide absorbed in the early stages of curing is small, and if it exceeds 300 parts by mass, the strength of the cementitious body using the carbon dioxide emission-reducing cement may decrease. The Portland cement or Portland cement clinker mentioned above includes various types of Portland cement such as ordinary, rapid-strength, moderate-heat, and low-heat cements, and their respective cement clinkers. The cement composition may also contain one or more admixtures such as blast furnace slag powder, fly ash, silica powder, and limestone powder, depending on the required strength development, durability, and workability.
[0027] Furthermore, the method for mixing Portland cement or Portland cement clinker with carbon dioxide emission reduction cement is not particularly limited and includes methods such as simultaneously grinding Portland cement or Portland cement clinker and carbon dioxide emission reduction cement, or grinding Portland cement or Portland cement clinker and then mixing the ground Portland cement or Portland cement clinker with carbon dioxide emission reduction cement.
[0028] 3. Cementaceous hardened body The cementitious hardened body of the present invention contains 25 to 70 parts by mass of water and aggregate per 100 parts by mass of the cement composition. The aggregates mentioned above include commonly used limestone aggregates, river sand, mountain sand, land sand, sea sand, crushed sand, silica sand, slag, lightweight fine aggregates, and mixtures thereof, as well as clinker aggregates and aggregates (CCU aggregates) in which carbon dioxide has been fixed, selected from recycled aggregates, waste concrete, blast furnace slag, and steelmaking slag. Furthermore, when the cementitious body contains coarse aggregate, the fine aggregate ratio (s / a) is preferably 5 to 70%, more preferably 10 to 60%. If the fine aggregate ratio is within the above range, the workability and ease of molding of the mortar or concrete will be improved. Furthermore, the content ratio of the aggregate in the cementitious hardened body (the total amount if fine aggregate and coarse aggregate are used in combination) is preferably 200 to 750 parts by mass, more preferably 200 to 650 parts by mass, per 100 parts by mass of the cement composition. If the content ratio is within the above range, the strength of the carbonation-cured cementitious hardened body will be high, and the shrinkage rate of the hardened body will be low.
[0029] Next, the clinker aggregate and CCU aggregate will be described. (i) Clinker aggregate The clinker aggregate is an aggregate containing C2S and C2AS, wherein the C2AS content is 5 to 100 parts by mass per 100 parts by mass of C2S, and it does not contain C3A, or contains 20 parts by mass or less of C3A per 100 parts by mass of C2S. When the C2AS content is 5 parts by mass or more, even at high firing temperatures, the amount of free lime (unreacted CaO) does not increase easily, making firing easier, and the amount of carbon dioxide absorbed increases. When the C2AS content is 100 parts by mass or less, the amount of molten material generated at high temperatures during the production of the clinker aggregate decreases, thus widening the temperature range in which firing is possible. In addition, because the amount of C2S is relatively high, the strength of the cementitious hardened body at the time of demolding is increased during the demolding process of the cementitious hardened body. The ratio of C2AS to 100 parts by mass of C2S is preferably 6 to 75 parts by mass, more preferably 7 to 50 parts by mass, even more preferably 8 to 40 parts by mass, and particularly preferably 12 to 30 parts by mass.
[0030] The clinker aggregate is preferably free of C3A (aluminate phase) or contains 20 parts by mass or less of C3A per 100 parts by mass of C2S, from the viewpoint of improving the fluidity of the hydraulic composition. If the C3A content exceeds 20 parts by mass, the fluidity of the mortar or concrete may decrease. When the clinker aggregate contains C3A, the amount of C3A per 100 parts by mass of C2S is more preferably 15 parts by mass or less, even more preferably 10 parts by mass or less, and particularly preferably 5 parts by mass or less.
[0031] From the viewpoint of increasing the strength of the carbon-cured cementitious hardened body, the C2S content in the clinker aggregate is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. Furthermore, the C2AS content in the clinker aggregate is preferably 5 to 25% by mass, more preferably 6 to 20% by mass, and even more preferably 7 to 15% by mass. When the C2AS content is 5% by mass or more, the amount of free lime in the aggregate does not increase easily, and the amount of carbon dioxide absorbed increases. When the C2AS content is 25% by mass or less, the strength of the carbon-cured cementitious body increases. The mineral composition of clinker aggregate (the proportions of C2S, C2AS, and C3A by mass) can be determined using the same method as for the mineral composition of clinker powder.
[0032] The free lime content in the clinker aggregate is preferably 2% by mass or less, and more preferably 0.2 to 1.5% by mass, from the viewpoint of preventing expansion and deterioration of the aggregate. Furthermore, in addition to the aforementioned C2S, the minerals in the clinker aggregate include C4AF, 12CaO·7Al2O3(C 12 A7) One or more selected from mullite, anorthite, amorphous phase, SiO2, cristobalite, lanquinite, and wollastonite, etc. The total proportion of substances other than C2S, C2AS, and C3A in the clinker aggregate is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.
[0033] Examples of methods for producing the clinker aggregate include a firing step of firing aggregate material containing one or more types selected from industrial waste, general waste, and construction excavated soil at 1250 to 1500°C to obtain a fired product, a crushing step of crushing the fired product to obtain crushed material, and a classification step of classifying the crushed material to obtain clinker aggregate. The aforementioned aggregate material for firing, the firing temperature of the material, and the firing method are the same as those used for firing clinker material, the firing temperature of the material, and the firing method in general cement production. Furthermore, in the classification process, by adjusting the particle size of the crushed material using general classification methods such as sieving, clinker aggregate can be obtained as coarse aggregate or fine aggregate with a desired particle size distribution. Furthermore, clinker obtained in the conventional cement clinker firing process may be used as the pulverized product in the firing process of the aforementioned product. The aforementioned clinker aggregate can be used as either fine aggregate or coarse aggregate, but from the viewpoint of fixing more carbon dioxide, it is preferable to use it as fine aggregate. Furthermore, when the fine aggregate contains both clinker aggregate and other aggregates, the clinker aggregate content in the total amount of fine aggregate is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 80% by mass or more. A clinker aggregate content of 40% by mass or more allows for the fixation of more carbon dioxide.
[0034] (ii) CCU aggregate As described above, CCU aggregate is an aggregate made by fixing carbon dioxide present in exhaust gases and the atmosphere to one or more materials selected from recycled aggregate, waste concrete, blast furnace slag, and steelmaking slag. From the viewpoint of reducing carbon dioxide emissions, it is the most preferable aggregate. In the production of CCU aggregate, methods for fixing carbon dioxide to the aggregate include, but are not limited to, methods such as fixing carbon dioxide to the aggregate in the presence of hot water or steam at 80-120°C and carbon dioxide. Steelmaking slag contains free CaO, which gives it expansive properties. If used directly in mortar or concrete, it can lead to deterioration phenomena such as pop-out. However, fixing carbon dioxide into steelmaking slag converts the free CaO into calcium carbonate, making it non-expandable and suitable for use as aggregate in mortar and concrete. Furthermore, the aforementioned CCU aggregate has fixed carbon dioxide present in exhaust gases and the atmosphere, and is a carbon-negative material (a state in which the amount of carbon dioxide absorbed is greater than the amount of carbon dioxide emitted during production). Therefore, by using it as an aggregate, the amount of carbon dioxide emitted during the production of mortar and concrete can be reduced. Furthermore, while the CCU aggregate can be used as either fine aggregate or coarse aggregate, it is preferable to use it as fine aggregate because it can fix more carbon dioxide. Furthermore, when the fine aggregate contains both CCU aggregate and other aggregates, the CCU aggregate content in the total amount of fine aggregate is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 80% by mass or more. A content of 40% by mass or more allows for the fixation of more carbon dioxide.
[0035] (iii) Other materials Furthermore, the cementitious hardened body may contain, depending on the purpose, various admixtures such as air-entraining agents, water-reducing agents, high-performance water-reducing agents, high-performance air-entraining agents, defoaming agents, shrinkage-reducing agents, silica fume, and metakaolin, as well as organic fibers and glass fibers, within a range that does not hinder the objectives of the present invention.
[0036] The BET specific surface area of the silica fume, which is another material to be incorporated into the cementitious hardened body of the present invention, is preferably 12 to 25 m². 2 The BET specific surface area is / g. Silica fumes with a BET specific surface area outside the above range are difficult to obtain. The BET specific surface area is more preferably 13 to 20 m². 2 The bulk density is 0.4 to 0.8 g / cm³. Furthermore, among the silica fumes mentioned above, one or more are particularly preferably selected from granular silica fume and aggregated silica fume. Here, granular silica fume refers to the silica fume described in JIS A 6207. The bulk density of the granular silica fume used in this invention is preferably 0.4 to 0.8 g / cm³. 3 Therefore, granular silica fume with a bulk density outside this range is difficult to obtain. Furthermore, the aggregated silica fume is, for example, silica fume in which the content of particles with a particle size of 1 μm or larger is 20% by mass or more, as measured by a laser diffraction / scattering particle size distribution analyzer.
[0037] (iv) Carbonation curing of cementitious bodies The cementitious cured material of the present invention, when subjected to carbonation curing, fixes carbon dioxide, densifying its structure and improving its strength. From the viewpoint of improving strength, the amount of carbon dioxide fixed in the carbonation-cured cementitious cured material is preferably 1 m³ of cementitious cured material. 3 They weigh between 80 and 200 kg each.
[0038] Furthermore, in addition to the method of curing cementitious hardened material by carbon dioxide exposure, the carbonation curing method also includes a method of blowing carbon dioxide into the mixture during the mixing of mortar or concrete, etc., from the viewpoint of absorbing more carbon dioxide. It should be noted that carbonation of cementitious hardened material can also occur naturally over a long period of time by absorbing carbon dioxide in the form of concrete products, concrete structures, or concrete pavements.
[0039] Furthermore, the concentration of carbon dioxide gas in the carbonation curing process is preferably 1% by volume or more, more preferably 10% by volume or more, even more preferably 50% by volume or more, and particularly preferably 60% by volume or more. If the concentration is 1% by volume or more, more carbon dioxide can be absorbed in the carbonation curing process. While a higher carbon dioxide concentration results in greater carbon dioxide absorption, from the viewpoint of reducing curing equipment costs, the carbon dioxide gas concentration is preferably 90% by volume or less, more preferably 85% by volume or less, and even more preferably 80% by volume or less.
[0040] Furthermore, the temperature in the carbonation curing process is preferably 5 to 100°C, more preferably 10 to 70°C, even more preferably 15 to 50°C, and particularly preferably 20 to 35°C. When the temperature is 5°C or higher, the efficiency of carbonation and the strength of the cementitious hardened material are higher, and when it exceeds 100°C, the energy cost of carbonation curing becomes excessive. Furthermore, the relative humidity in the carbonation curing process is preferably 20-90%, more preferably 30-80%, and particularly preferably 40-70%. When the relative humidity is 20% or higher, the efficiency of carbonation and the strength of the cementitious hardened material are higher, while when it exceeds 90%, the costs associated with equipment and other factors become excessive.
[0041] 4. Method for manufacturing calcined products The calcined product used in this invention can be manufactured by firing at 1000 to 1350°C using one or more materials selected from industrial waste, general waste, and construction-generated soil as raw materials. The manufacturing method includes (a) a raw material mixing step, (b) a firing and cooling step as essential steps, and (c) a grinding step as an optional step. The reason the grinding step is optional is that in the manufacture of carbon dioxide emission-reducing cement, if the fired product is mixed with a mixed material such as fine limestone powder and then ground (simultaneous grinding), the grinding step becomes unnecessary in the manufacture of the fired product.
[0042] The following describes (a) the raw material blending process, (b) the firing and cooling process, and (c) the grinding process. (a) Raw material blending process In this process, one or more types of waste selected from industrial waste, general waste, and construction-generated soil are used as raw materials and blended to achieve a mineral composition within the range of the aforementioned calcined product. Using the aforementioned waste as raw materials is preferable from the viewpoint of effective waste utilization. The aforementioned industrial waste includes coal ash, ready-mix concrete sludge, concrete waste, water treatment sludge, construction sludge, steelmaking sludge, construction waste, foundry sand, rock wool, waste glass, blast furnace secondary ash, and boring waste soil. The aforementioned general waste includes sewage sludge, municipal solid waste incineration ash, dry sewage sludge powder, seashells, and sewage sludge incineration ash. Furthermore, the aforementioned construction-generated soil includes soil, excavated soil, and waste soil generated from construction sites and other construction sites.
[0043] Furthermore, if it is difficult to formulate the calcined product so that its mineral composition falls within the specified range using only the aforementioned waste materials, natural raw materials such as calcium raw materials, silicon raw materials, aluminum raw materials, and iron raw materials may be used to supplement it. Here, examples of calcium raw materials include limestone, quicklime, slaked lime, and steelmaking slag; examples of silicon raw materials include silica and clay; examples of aluminum raw materials include clay; and examples of iron raw materials include iron slag and iron cake.
[0044] Furthermore, if it is necessary to adjust the particle size of the raw materials, they may be ground to a predetermined particle size using a pulverizer such as a ball mill. In addition, the raw materials may be granulated to facilitate firing. Examples of granulation methods include rolling granulation, extrusion granulation, and compression granulation.
[0045] (b) Firing / cooling process The aforementioned blended raw materials are fired in a firing furnace such as a rotary kiln, and then cooled in a cooler to obtain a fired product. Here, the firing temperature of the fired product is 1000 to 1450°C. If the firing temperature is below 1000°C, it is difficult to reduce the free lime in the fired product, and if it exceeds 1450°C, the raw materials may melt and the amount of fired product may decrease. The firing temperature is preferably 1150 to 1350°C, and more preferably 1200 to 1350°C. Furthermore, the firing time is preferably 30 to 150 minutes. If the time is less than 30 minutes, the firing is insufficient, and if it exceeds 150 minutes, productivity decreases. More preferably, the firing time is 40 to 120 minutes. Furthermore, while there are no particular restrictions on the firing furnace, a rotary kiln is preferred because it allows for continuous production and offers high manufacturing efficiency. In addition to heavy oil, fuel alternatives such as coal, waste oil, waste tires, and waste plastics can also be used for firing. The mineral composition of the calcined product (percentages of C2S, C2AS, C4AF, and C3A by mass) can be calculated from the percentages of CaO, SiO2, Al2O3, and Fe2O3 in the raw materials or the calcined product by mass using the following formula. C2S=1.02×CaO+0.95×SiO2-1.69×Al2O3-0.36×Fe2O3 C2AS=-1.63×CaO+3.04×SiO2+2.69×Al2O3+0.57×Fe2O3 C4AF = 3.04 × Fe2O3 C3A = 1.61 × CaO - 3.00 × SiO2 - 2.26 × Fe2O3 (However, if C3A is negative, C3A is considered to be "0".)
[0046] (c) Grinding process The grinding method is not particularly limited; for example, it may be ground using a grinder such as a ball mill or rod mill. Furthermore, the Blaine specific surface area of the pulverized material is preferably 2500 to 5000 cm² to promote the hydration reaction, increase carbon dioxide absorption, and improve the strength development of the cementitious hardened body. 2 / g, more preferably 3000-4500cm 2 It is / g. Furthermore, in order to improve the efficiency of the grinding, it is preferable to add a grinding aid during grinding. Examples of such grinding aids include diethylene glycol, triethanolamine, and triisopropanolamine. The amount of these grinding aids added is preferably 0.01 to 1 part by mass per 100 parts by mass of the calcined product. [Examples]
[0047] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. 1. Manufacturing of C2AS-containing calcined products Sewage sludge, construction waste soil, limestone, and clay were used as raw materials and mixed according to the chemical composition shown in Table 1. These mixtures were then fired in a rotary kiln at the temperatures shown in Table 1 to obtain the C2AS-containing calcined products shown in Table 2. In addition to heavy oil, waste oil and waste plastics were used as fuel for the calcination. Furthermore, the mineral composition of the C2AS-containing calcined material shown in Table 2 was calculated using the following method: (i) After crushing the C2AS-containing calcined material, powder X-ray diffraction (XRD) patterns were obtained using a D8 ADVANCE A-25 (Bruker Japan). (ii) The measurement conditions for the powder XRD are: target CuKα, tube conditions 40kV-40mA, scanning range 2θ=5~65°, step width 0.023° / step, and measurement time 0.13 seconds / step. (iii) Qualitative analysis of the XRD pattern using DIFFRAC.EVA (Bruker Japan) revealed peaks for C2S(β-C2S), C2AS, and C4AF. Then, using DIFFRAC.TOPAS ver.6 (Bruker Japan), the Rietveld method was used to fit the theoretical profiles of each mineral C2S(β-C2S), C2AS, and C4AF to the experimentally measured profiles obtained from the powder XRD results, thereby determining the content of each mineral phase.
[0048] [Table 1]
[0049] [Table 2]
[0050] 2. Manufacturing of C2AS-containing cement To 100 parts by mass of the C2AS-containing calcined product, 2.0 parts by mass of dihydrate gypsum (SO3 equivalent) were added, and then the calcined product and dihydrate gypsum were simultaneously ground in a batch-type ball mill to obtain a Blaine specific surface area of 3400 ± 200 cm². 2 We manufactured cement containing C2AS at a concentration of / g.
[0051] 3. Manufacturing of mortar specimens According to the mortar mix shown in Table 3, the following ingredients were added in order to a 20-liter Hobart mixer at 20±3°C for 30 seconds: (B) the C2AS-containing cement, blast furnace slag powder, and ordinary Portland cement with the chemical composition shown in Table 5 (corresponding to the cement composition of the present invention: example), followed by the remaining half amount of mountain sand, and then dry-mixed for 30 seconds. Similarly, the following ingredients were added in order to a 20-liter Hobart mixer at 20±3°C for 30 seconds: (B) the C2AS-containing cement and ordinary Portland cement (cement, comparative example), followed by the remaining half amount of mountain sand, and then dry-mixed for 30 seconds at 20±3°C. Next, while mixing each of the aforementioned materials, water containing the admixture was added to each, and the mixture was kneaded for another 60 seconds to remove the mortar. Then, it was kneaded for another 60 seconds to discharge, thereby producing each batch of fresh mortar (however, the mixing volume for one batch was 4 liters).
[0052] [Table 3]
[0053] [Table 4]
[0054] [Table 5]
[0055] Next, using the fresh mortar described above, mortar specimens with a diameter of 5 cm and a length of 10 cm were produced by demolding two days after placement in accordance with JIS A 1132 "Method for preparing test specimens for concrete strength testing". The demolding properties of the mortar are shown in Table 8 below. Next, the specimens were subjected to carbonation curing at a carbon dioxide concentration of 80% by volume, a temperature of 30°C, and a relative humidity of 60%, and then to underwater curing at a temperature of 20°C, until the ages shown in Table 8. However, the ages shown in Table 8 represent the number of days from the start of curing.
[0056] 3. Manufacturing of concrete test specimens According to the concrete mix design shown in Table 6, the following ingredients were added in order to a 55-liter pan-type mixer (manufactured by Taiheiyo Kiko Co., Ltd.) in a room at 20±3℃ and a relative humidity of 80% or higher: coarse aggregate, mountain sand (half the total amount), ordinary Portland cement alone, or cement consisting of ordinary Portland cement and C2AS-containing cement, and the remaining half the amount of mountain sand. The mixture was then dry-mixed for 30 seconds. Next, while mixing the aforementioned materials, water containing the admixture was added, and the mixture was kneaded for another 60 seconds to remove the concrete. Then, it was kneaded for another 60 seconds and discharged to produce fresh concrete.
[0057] [Table 6]
[0058] [Table 7]
[0059] Next, using the fresh concrete, the slump was measured in accordance with JIS A 1101 "Test Method for Slump of Concrete," and the air content was measured in accordance with JIS A 1128 "Test Method for Air Content of Fresh Concrete by Pressure - Air Chamber Pressure Method." These results are shown in Table 9 below.
[0060] Furthermore, using the aforementioned fresh concrete, concrete specimens with a diameter of 10 cm and a length of 20 cm were manufactured by demolding one day after placement in accordance with JIS A 1132 "Method for preparing test specimens for concrete strength testing". Next, the specimens were subjected to carbonation curing at a carbon dioxide concentration of 80% by volume, a temperature of 30°C, and a relative humidity of 60%, and to underwater curing at a temperature of 20°C, up to the ages shown in Table 9. However, the starting point for the curing period was the time of concrete demolding for carbonation curing and the time of concrete placement for underwater curing.
[0061] 4. Measurement of compressive strength of mortar and concrete specimens The compressive strength of the mortar specimens was measured at the ages shown in Tables 8 and 9, respectively, in accordance with JSCE-G 505 "Draft Method for Testing the Compressive Strength of Mortar or Cement Paste Using Cylindrical Specimens," and the compressive strength of the concrete specimens was measured in accordance with JIS A 1108 "Method for Testing the Compressive Strength of Concrete." The results are shown in Tables 8 and 9, respectively. As shown in Table 8, the embodiments of the present invention, despite containing blast furnace slag which would normally lead to a decrease in compressive strength, exhibited a compressive strength comparable to that of the comparative examples.
[0062] [Table 8]
[0063] [Table 9]
[0064] 5. Measurement of carbonation depth in mortar and concrete specimens The carbonation depth of both the mortar and concrete specimens was measured in accordance with JIS A 1152, "Method for measuring the carbonation depth of concrete." Specifically, after the carbonation curing period of 3, 7, 14, and 28 days, the mortar and concrete specimens were cut using a cutting machine at the midpoint of their height, as shown in Figure 1. The cut surface was then cleaned using an air blower and a brush to prepare the measurement surface. Next, phenolphthalein solution was sprayed onto the measurement surface, and the distance from the side of the specimen to the reddish-purple area at eight points was measured in 0.5 mm units using calipers, as shown in Figures 1 and 2, and the average was calculated to determine the carbonation depth. For specimens aged 14 days and 28 days, the specimens used were those after the compressive strength had been measured, and only the levels at which coloration was observed at those ages were measured. These results are shown in Tables 10 and 11.
[0065] [Table 10]
[0066] [Table 11]
[0067] 6. Measurement of carbon dioxide fixation (1) Preparation of the sample (i) Mortar and concrete The carbonation-cured mortar and concrete specimens were coarsely crushed using a pressure press, and then further crushed to a size of 5 mm or less using a jaw crusher. After reducing this to approximately 50 g, it was finely ground using a disc-type vibratory mill and used to measure the amount of carbon dioxide fixed. (ii) Coarse aggregate and fine aggregate The coarse and fine aggregates were crushed to a size of 5 mm or less using a jaw crusher. After reducing this to approximately 50 g, the resulting material was finely ground using a disc-type vibratory mill and then subjected to measurement. (iii) Cement composition and cement The sample was used as is for measurement.
[0068] (2) Quantitative analysis of carbon The carbon content of mortar, concrete, coarse aggregate, fine aggregate, cement composition, and cement was determined using the carbon meter described below. The conditions for this determination are shown below. Measurement device: Carbon and sulfur analyzer EMIA-Step (manufactured by Horiba, Ltd.) Measurement method: Combustion in an oxygen stream - infrared absorption method, temperature 1250°C, time 120 seconds. Heating method: A tubular electric resistance heating furnace system was used, and magnesium perchlorate was used as the dehydrating agent.
[0069] (3) Calculation of carbon dioxide fixation The amount of carbon dioxide fixed was calculated according to the following steps (i)→(ii)→(iii). The weight of the specimens was measured before and after curing. (i) The amount of carbon dioxide contained in the specimen after carbonation curing (amount of carbon dioxide after curing) was calculated using the following formula (1). TIFF0007943728000012.tif12137 (ii) The amount of carbon dioxide contained in the specimen before carbonation curing (amount of carbon dioxide before curing) was calculated using the following formula (2). TIFF0007943728000013.tif44134 (iii) The difference between the amount of carbon dioxide after curing and the amount of carbon dioxide before curing, calculated using equations (1) and (2) above, was taken as the amount of carbon dioxide fixed in the specimen and calculated using the following equation (3). TIFF0007943728000014.tif8137 The amount of carbon dioxide fixed per ton of cement composition and cement (kg / t-B and kg / t-C, respectively) was calculated using the following formula (4). 3 Carbon dioxide fixation rate per unit area (in kg / m³) 3 ―M, and kg / m 3 The amount of carbon dioxide fixed in the specimen was determined by dividing the volume of the specimen with a diameter of 10 cm and a length of 20 cm, and the volume of the specimen with a diameter of 5 cm and a length of 20 cm. TIFF0007943728000015.tif25150 The amounts of carbon dioxide fixed are shown in Tables 10 and 11 above. As shown in Table 10, there was no difference in the amount of carbon dioxide fixed between the examples and the comparative examples.
[0070] 7. Calculation of the carbon dioxide emission reduction rate The carbon dioxide emission reduction rate was calculated using the following formula. Carbon dioxide emission reduction rate = [Emission intensity of ordinary Portland cement (kg / t) - Emission intensity of ordinary Portland cement (kg / t) × Mass fraction of ordinary Portland cement in the cement composition - Emission intensity of C2AS-containing cement (kg / t) × Mass fraction of C2AS-containing cement in the cement composition - Emission intensity of blast furnace slag powder (kg / t) × Mass fraction of blast furnace slag powder in the cement composition + Amount of carbon dioxide fixed (kg / t)] / Emission intensity of ordinary Portland cement (kg / t) × 100 For ordinary Portland cement, the carbon dioxide emission intensity used was the value (762.7 kg / t) listed in the Cement Association's "Summary of Cement LCI Data." Furthermore, the carbon dioxide emission intensity of the C2AS-containing cement was calculated using the following procedure (a) to (g), resulting in a value of 560.6 kg / t. (a) The energy required to manufacture ordinary Portland cement was calculated using the heat for clinker firing specified in JIS R 0303. (b) The amount of carbon dioxide emissions from fossil fuels emitted when ordinary Portland cement is produced was calculated by multiplying the energy required to produce ordinary Portland cement by the "emission factor" for burning coal. (c) The carbon dioxide emissions from fossil fuels (283.6 kg / t-cement) shown in the Cement Association's "Summary of Cement LCI Data" were divided by the calculated carbon dioxide emissions (the value calculated in (b) above) to obtain the "kiln efficiency coefficient". (d) The energy required to produce C2AS-containing cement was calculated using the heat required for clinker firing as specified in JIS R 0303. (e) The amount of carbon dioxide emissions from fossil fuels emitted when manufacturing cement containing C2AS was calculated by multiplying the required energy (the value calculated in (d) above) by the "emission factor" and the "kiln efficiency factor". (f) The amount of carbon dioxide emitted from the decarboxylation of raw materials was calculated from the amount of carbon dioxide contained in each raw material and the blending ratio in the production of C2AS-containing cement. (g) The sum of carbon dioxide emissions from fossil energy (the value calculated in (e) above) and carbon dioxide emissions from raw material decarboxylation (the value calculated in (f) above) during the production of C2AS-containing cement was calculated to determine the carbon dioxide emission intensity of C2AS-containing cement. The carbon dioxide emission intensity for blast furnace slag fine powder was assumed to be 0 kg / t. The carbon dioxide emission reduction rates are shown in Table 12 for mortar and in Table 13 for concrete. As shown in Table 12, the embodiments of the present invention show a higher reduction in carbon dioxide emissions compared to the comparative examples.
[0071] [Table 12]
[0072] Table 13
Claims
1. A carbon dioxide emission reduction cement composition comprising 43 to 82 parts by mass of ordinary Portland cement per 100 parts by mass of the carbon dioxide emission reduction cement described below (A). (A) Carbon dioxide emission reduction cement: See (B) C below 2 Cement containing 52 to 174 parts by mass of blast furnace slag fine powder per 100 parts by mass of AS-containing cement. (B) C 2 AS-containing cement: Cement containing fired products containing (a) to (c) below and gypsum. (a) 2CaO・SiO 2 3CaO·Al per 100 parts by mass 2 O 3 0 parts by mass (b) 2CaO·SiO 2 relative to 100 parts by mass, 2CaO·Al 2 O 3 ·SiO 2 and 4CaO·Al 2 O 3 ·Fe 2 O 3 in a total amount of 30 to 49.4 parts by mass (c) 2CaO・Al 2 O 3 SiO 2 4CaO·Al per 100 parts by mass 2 O 3 Fe 2 O 3 0 to 0.61 parts by mass
2. A cementitious hardened body comprising 100 parts by mass of the carbon dioxide emission-reducing cement composition according to claim 1, 25 to 70 parts by mass of water, and aggregate.
3. The cementitious hardened body according to claim 2, wherein the aggregate is one or more aggregates selected from clinker aggregate, recycled aggregate, waste concrete, blast furnace slag, and steelmaking slag, on which carbon dioxide has been fixed.
4. The cementitious hardened body according to claim 2 or 3, wherein the cementitious hardened body is a cementitious hardened body that has been cured by carbonation.
5. The cementitious hardened body is a cementitious hardened body 1 m 3 The cementitious hardened body according to claim 4, wherein the cementitious hardened body has fixed 80 to 200 kg of carbon dioxide per unit area.
Citation Information
Patent Citations
Production process of cement-based hardened body
JP2001261467A
Cement admixture
JP2004002155A
Concrete kneading material, co2 absorption precast concrete and method of producing the same
JP2011168436A
Hydraulic composition
JP2014051433A
Cement hardening body and manufacturing method therefor
JP2016047788A